DEVELOPMENT AND STRAPPING OF SOLAR HOT WATER SUPPLY IN THE EXAMPLE OF THE CITY OF NUKUS (Academicia Globe: Inderscience Research, 2023)
The article is devoted to the study of the operation of the installation and strapping of hot water supply based on a solar collector. The algorithm for calculating the efficiency of the installation is described step by step.